Meningkatkan Motivasi Belajar Pendidikan Agama Islam Tentang Berperilaku Rendah Hati dalam Kehidupan Sehari-Hari Studi Kasus Siswa Kelas V SDN 027 Labuhan Tangga Baru - Dedi Andrianto; Sudarwin Sudarwin; Wakib Kurniawan (STIKes Ibnu Sina Ajibarang, 2025)
The realization of learning that actively involves students is the hope of all parties, both the community and education practitioners. Increasing student activity is highly dependent on the teacher's ability to plan effective teaching and learning activities to achieve learning objectives. In the learning process at school, teachers need to encourage students to make optimal observations in order to obtain maximum learning outcomes. Therefore, teachers should provide students with the widest possible opportunity to observe in depth. The application of learning strategies with an activity-based approach in Islamic Religious Education subjects for grade V students of SDN 027 Labuhan Tangga Baru is expected to be able to increase motivation, achievement, creativity, and problem-solving abilities in learning.